2005
DOI: 10.1051/rnd:2005044
|View full text |Cite
|
Sign up to set email alerts
|

Maternal fish oil supplementation in lactation: effect on developmental outcome in breast-fed infants

Abstract: -Docosahexaenoic acid (DHA) accumulates in the brain during the 1st and 2nd years of life. The objective of this study was to see if an increased content of DHA in breast-milk via maternal fish oil (FO)-supplementation affects mental development in term infants. one hundred twenty-two Danish mothers with a habitual fish intake below the population median were randomized to 4.5 g·d -1 of FO or olive oil (OO) for the first four months of lactation. Fifty-three mothers with habitual fish intake in the highest qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 36 publications
4
102
3
2
Order By: Relevance
“…In addition, Church et al [41] showed that excess as well as deficient n-3 fatty acid intakes during pregnancy and lactation cause impaired neural transmission in rats [41]. In human infants, negative associations between higher DHA intakes and verbal skills have been reported [42,43]. What brain areas are involved in the ascending part of the curve might become suggested from studies in newborn baboons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Church et al [41] showed that excess as well as deficient n-3 fatty acid intakes during pregnancy and lactation cause impaired neural transmission in rats [41]. In human infants, negative associations between higher DHA intakes and verbal skills have been reported [42,43]. What brain areas are involved in the ascending part of the curve might become suggested from studies in newborn baboons.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have ruled out confounding variables such as maternal size, age, parity, health, smoking and alcohol consumption [18,21] as well as methylmercury and other contaminants [17]. Adverse effects from excess ω-3 FA consumption by infants through infant formulas that are fortified with ω-3 FA include reduced body growth and head circumference [10,12], decreased blood arachidonic acid (AA) levels [7] and decreased verbal skills [26,42]. Two studies found prolonged ABR latencies in the children born to women who consumed large amounts of seafood [27][28].…”
Section: Introductionmentioning
confidence: 99%
“…17 An estimated 30-fold increase in the amount of DHA and AA in the infant forebrain occurs between the last trimester of pregnancy and the first 2 years of life. 18,19 A series of randomized, double-blinded, placebo-controlled trials have been conducted in recent years to determine whether infants fed formula supplemented with LCPUFAs would have improved performance on measures of cognition compared with infants fed typical formula. Results of these trials have varied widely, with some trials demonstrating improved cognitive abilitiesin infantsfed formula supplemented with LCPUFAs 14,20-23 and other trials demonstrating no effect.…”
mentioning
confidence: 99%